Changing surface water conditions for the last 500 ka in the Southeast Atlantic: Implications for variable influences of Agulhas leakage and Benguela upwelling. (11th September 2015) - Petrick, Benjamin F.; McClymont, Erin L.; Marret, Fabienne; van der Meer, Marcel T. J.
Abstract The Southeast Atlantic Ocean is an important component of global ocean circulation, as it includes heat and salt transfer into the Atlantic through the Agulhas leakage as well as the highly productive Benguela upwelling system. Here we reconstruct sea surface temperatures (SSTs) from Ocean Drilling Program (ODP) Site 1087 in the Southeast Atlantic to investigate surface ocean circulation patterns during the late Pleistocene (0–500 ka). The UK′37 index and dinoflagellate cyst assemblages are used to reconstruct SSTs, δDalkenone is used to reconstruct changes in sea surface salinity, and mass accumulation rates of alkenones and chlorine pigments are quantified to detect changing marine export productivity. The greatest amplitude of SST warming precedes decreases in benthic δ18O and therefore occurs early in the transition from glacials to interglacials. The δDalkenone, as a salinity indicator, increases before SSTs, suggesting that the pattern of Agulhas leakage is more complex than suggested by SST proxies. Marine isotope stage (MIS) 10 shows an anomalous pattern: it is marked by a pronounced increase in chlorine concentration, which may be related to enhanced/expanded Benguela upwelling reaching the core site. We find no evidence of an absence of Agulhas leakage throughout the record, suggesting that there is no Agulhas cutoff even during MIS 10. Finally, the ODP Site 1087 record shows an increasing strength of Agulhas leakage towards the present day, which may have impacted the intensity of the Atlantic meridional overturning circulation. As a result, the new analyses from ODP Site 1087 demonstrate a complex interaction between influences of the Benguela upwelling and the Agulhas leakage through the late Pleistocene, which are inferred here to reflect changing circulation patterns in the Southern Ocean and in the atmosphere.